Multi-model projections of stratospheric ozone in the 21st century - Eyring, Veronika (2007)
Simulations of the recent past from thirteen coupled chemistry-climate models (CCMs) participating in the CCM Validation Activity for SPARC (CCMVal) are evaluated to provide guidance for the interpretation of ozone projections made by the same CCMs. Several different diagnostics are used to evaluate temperature, trace species and ozone in the models. The core period of the evaluation is from 1980 to 1999 but long-term trends are compared for an extended period (1960-2004). Most CCMs show reasonable agreement with observed total ozone trends and variability on a global scale, but a greater spread in the ozone trends in polar regions in spring. Global long-term stratospheric temperature trends are in reasonable agreement with satellite and radiosonde observations. The simulated ozone evolution in the 21st century in the CCMs is mainly determined by decreases in halogen concentrations and continued cooling of the global stratosphere due to increases in greenhouse gases. Differences in stratospheric inorganic chlorine (Cly) among the models are key to diagnosing the inter-model differences in simulated ozone hole recovery. It is found that there are substantial quantitative differences in the simulated Cly, with the October mean Antarctic Cly peak value varying from less than 2 ppb to over 3.5 ppb in the CCMs, and the date at which the Cly returns to 1980 values varying from before 2030 to after 2050. There is a corresponding large range in the timing of recovery of Antarctic ozone back to 1980 values.